2003
DOI: 10.1161/01.cir.0000058706.82623.a1
|View full text |Cite
|
Sign up to set email alerts
|

Lower Incidence of Thrombus Formation With Cryoenergy Versus Radiofrequency Catheter Ablation

Abstract: Background-Radiofrequency (RF) catheter ablation is limited by thromboembolic complications. The objective of this study was to compare the incidence and characteristics of thrombi complicating RF and cryoenergy ablation, a novel technology for the catheter-based treatment of arrhythmias. Methods and Results-Ablation lesions (nϭ197) were performed in 22 mongrel dogs at right atrial, right ventricular, and left ventricular sites preselected by a randomized factorial design devised to compare RF ablation with cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
335
2
8

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 447 publications
(376 citation statements)
references
References 41 publications
24
335
2
8
Order By: Relevance
“…When hyperthermia techniques are performed, it is difficult to determine the margin of the cytotoxic effects of heat ablation and overheating may occur [40,[46][47]. This can generate a residual heat load in the tissue that remains for an extended period of time and slowly dissipates into the tissue, resulting in continued damage, lesion expansion, thrombus formation, strictures, and other complications [40,[46][47][48][49][50]. If a double heat exposure is applied, this effect intensifies, further damaging the surrounding tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When hyperthermia techniques are performed, it is difficult to determine the margin of the cytotoxic effects of heat ablation and overheating may occur [40,[46][47]. This can generate a residual heat load in the tissue that remains for an extended period of time and slowly dissipates into the tissue, resulting in continued damage, lesion expansion, thrombus formation, strictures, and other complications [40,[46][47][48][49][50]. If a double heat exposure is applied, this effect intensifies, further damaging the surrounding tissues.…”
Section: Discussionmentioning
confidence: 99%
“…If a double heat exposure is applied, this effect intensifies, further damaging the surrounding tissues. This continued destruction, while positive in diseased tissue, is difficult to monitor and control and may result in a high degree of heat based complications, such as hematoma and neoplasia [48][49][50][51][52]. The addition of the freezing step after heating could theoretically remove residual heat load remaining following hyperthermia, potentially reducing the risk of collateral damage and unwanted complications to surrounding tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The result is that the extracellular matrix and scaffold structure of the nerves and vessels remain intact, allowing the affected axon/myelin sheath or vascular cells to regenerate and repair the injury site. In comparison, heat lesions have been found to not only destroy cells but also disrupt the structural matrix, resulting in a narrower therapeutic window [33][34][35]. A recent study [36] demonstrated that following a traumatic peripheral nerve injury, the regenerated myelin sheath was thinner and exhibited a decreased intermodal length.…”
Section: Safety Of Cryoneurolysismentioning
confidence: 99%
“…In this same study, it was found that the small arterioles in proximity to the treatment site showed rare fibrinoid degeneration, but their lumens remained patent. Khairy [35] examined the effects of treating atrial and ventricular structures in a canine model with various cooling rates to −55°and −75°C, revealing that the underlying tissue and extracellular matrix architecture were preserved and there was no evidence of endocardial thrombus formation. These results hold even at colder temperatures: two studies which examined the effect of liquid nitrogen (−196°C) on canine carotid and femoral arteries (in vivo) [39] as well as the porcine vena cava [40] demonstrated necrosis of the affected cells, but the collagen and elastic structure remained largely intact.…”
Section: Safety Of Cryoneurolysismentioning
confidence: 99%
“…The CB patients had DC in 9 PVs (4.5%) of initially isolated PVs in 9 patients (18%), which was consistent of recent reported incidences by using second-generation CB of approximately 0~4.5% of the PVs in 0-12% of patients [18][19][20] . Although cryothermal energy is a milder and safer form of energy than RF energy, cryothermal energy creates well-delineated wider lesions with preservation of tissue structure as compared to RF which causes tissue disruption from excess heating and generation of inhomogeneous lesions 21,22) . Therefore, good quality of lesions by cryothermal energy may confer an infrequent incidence of ATP-provoked DC.…”
Section: Impact Of Different Technique Of Cb Ablation Vsmentioning
confidence: 99%